PENGARUH ENVIRONMENTAL COSTS DAN ENVIRONMENTAL PERFORMANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2019-2022 - Zahrani, Putri; Fitri, Yulia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to determine the effect of environmental cost and environmental performance on financial performance (ROA) in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research is quantitative. The population of this study is manufacturing companies listed on the IDX for the period 2019-2022, with a total population of 193 companies. The sampling method was purposive, consisting of 32 companies as research samples. The data used in this study is secondary data obtained from financial report documentation, annual reports published on the IDX website and company websites, and PROPER ratings published on the KLHK (Ministry of Environment and Forestry) website. The data analysis used is in the form of multiple linear regression using the SPSS 25 application. The study results show that environmental cost significantly affects financial performance (ROA), environmental performance has a significant effect on financial performance (ROA), meanwhile environmental cost and environmental performance significantly affect financial performance (ROA) in manufacturing companies listed on the IDX for 2019-2022.